Legal Convergence Related to Environmental Protection Policy with Investment Policy in Constitutional Perspective - Rodhi Agung Saputra; HS Tisnanta; Agus Triono; Kasmawati (Formosa Journal of Multidisciplinary Research, 2023)
This study is to examine the legal convergence related to environmental protection policies with investment policies in a constitutional perspective. The environment has become a supreme power in the constitutional life of Indonesia. The concept of environmental sovereignty is clearly regulated in Article 25A, Article 28H paragraph (1) and Article 33 paragraph (3) and (4). These articles provide green nuances to the 1945 Constitution, so that the implementation of the articles in the 1945 Constitution provides new thinking for lawmakers so that the concept of the environment can be realized in every law made. The problems that will be in this study are How is the Convergence of Law Related to Environmental Protection Policy with Investment Policy in Constitutional Perspective Environmental Protection Policy with Investment Policy. The research method used is a normative research method using a statute approach and analyzed using content analysis